Kraj-obrazy. Topografie w wybranych późnych utworach Elizy Orzeszkowej - Katarzyna Pastuszek (Postscriptum Polonistyczne)
The aim of the article is to reinterpret the landscapes created by Eliza Orzeszkowa with the use of the tools offered by geocritics and geopoetics. It enables treating topography as the main element of the literary landscape, which – in the case of Orzeszkowa – creates the landscape itself. Topography/’topographic experience’ contains the landscape and makes it visible. Using some selected examples, the author of the article explains how space has been created and which senses it evokes.